2023
DOI: 10.2174/1574886317666221010092132
|View full text |Cite
|
Sign up to set email alerts
|

Off-label Use of Oral Immunotherapy for Rhinoconjunctivitis and Asthma due to Grass Pollen: A Safe and Effective Alternative in Patients over 65 Years Old: A Series of Case Reports

Abstract: Introduction: Allergic rhinoconjunctivitis and asthma are the most common IgE-mediated diseases worldwide. Allergen-specific immunotherapy (AIT) is currently the only modifying treatment for these IgE-mediated diseases, in both children and adults. Subcutaneous immunotherapy is widely used, but in patients over 65 years old there may be an increased risk of adverse reactions and a worse response to treatment. Oral immunotherapy (OIT) has been proved to be effective and safe, but currently, in most countries, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Additionally, injection-caused pain may elicit resistance to SCIT in certain pediatric patients. A recent study has reported high safety and efficiency of OIT in elderly patients with allergic rhinoconjunctivitis and asthma due to grass pollen ( 7 ). In our study, OIT with enteric-coated capsules also showed stronger clinical efficacy and safety than SCIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, injection-caused pain may elicit resistance to SCIT in certain pediatric patients. A recent study has reported high safety and efficiency of OIT in elderly patients with allergic rhinoconjunctivitis and asthma due to grass pollen ( 7 ). In our study, OIT with enteric-coated capsules also showed stronger clinical efficacy and safety than SCIT.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration may be an alternative route of AIT ( 4 ). SCIT enhances the suppression on the proliferation of antigen-specific Th2-cells and the progressive increase of antigen-specific IgG, while oral immunotherapy (OIT) causes supplementary changes through the mucosa and/or regional lymph nodes ( 6 , 7 ). OIT can successfully desensitize allergic individuals to allergic foods, such as peanuts ( 8 ).…”
Section: Introductionmentioning
confidence: 99%